The intertidal Fortuyniidae (Acari: Oribatida): new species, morphological diversity, ecology and biogeography - Pfingstl, Tobias (Zootaxa, 2015)
Three new fortuyniid species, Fortuynia longiseta sp. nov., F. maledivensis sp. nov. and Alismobates pseudoreticulatus sp. nov., were found in littoral environments of the Maldives and Singapore and are described based on adult and juvenile morphology. A key is given to all Alismobates and Fortuynia species. The genus Fortuynia shows a homogeneous morphology and this is supposed to be a result of a limited habitat preference shown in this genus. Nearly all species only occur on rocky intertidal shores, except for F. rotunda dwelling in mangrove habitats and F. smiti found in riverine environments. Fortuynia smiti was now also found in a typical littoral habitat in Singapore and hence the remarkably broad ecological range of this species is discussed. The records of further fortuyniid species in the Indo-Pacific affirm that this taxon may be continuously distributed along shores of this geographic region.